Runoff Infiltration in Urban Green Space and Parameters of Sponge Facilities - Jiang Chunbo; Xu Wenbin; Gao Jiayu; Li Jiake; Liu Kehan; Dang Zhenguo (Shuitu baochi tongbao)
[Objective] The infiltration characteristics of urban green space runoff and the infiltration parameters for sponge facilities were studied in order to provide theoretical support for the construction of sponge facilities in built-up urban green space areas. [Methods] Taking Nanchang City, Jiangxi Province as a case area. Soil characteristic parameters were calculated by particle size distribution (PSD) and the soil-plant-air-water (SPAW) model. The Horton infiltration equations were fitted to single-ring infiltration field measurements of infiltration rate using Matlab to obtain the initial and stable infiltration rates and the attenuation coefficient. Soil water tension and unsaturated hydraulic conductivity were estimated by HYPROP2 and HYPROP-data evaluation software (HYPROP-DES). [Results] The stable infiltration rate was basically reached the stage of stable infiltration 5—10 min after the start of on-site infiltration, and most of the observed stable infiltration rates were less than 100 mm/h. The infiltration process was greatly affected by differences in hydrological soil groups and human disturbance. It took about seven days after full saturation for the infiltration rate of the soil to recover to the initial state. Based on the RECARGA model, a technical route for green space sponge facility reconstruction under the concept of sponge city was constructed. [Conclusion] The three methods can be used to deduce the process of urban green space soil infiltration and can improve the design accuracy of key parameters of sponge facilities. Initial water content and site factors need to be considered in the process of model calculations.